Genomic and Immunologic Correlates of Indoleamine 2,3-Dioxygenase Pathway Expression in Cancer - Panda, Anshuman; Ganesan, Shridar (Frontiers in Genetics, 2021)
Immune checkpoint blockade leads to unprecedented responses in many cancer types. An alternative method of unleashing anti-tumor immune response is to target immunosuppressive metabolic pathways like the IDO pathway. Despite promising results in Phase I/II clinical trials, an IDO-1 inhibitor did not show clinical benefit in a Phase III clinical trial. Since a treatment can be quite effective in a specific subset without being effective in the whole cancer type, it is important to identify the subsets of cancers that may benefit from IDO-1 inhibitors. In this study, we looked for the genomic and immunologic correlates of IDO pathway expression in cancer using the Cancer Genome Atlas dataset. Strong CD8+ T-cell infiltration, high mutation burden, and expression of exogenous viruses (EBV, HPV, HCV) or endogenous retrovirus (ERV3-2) were associated with over-expression of IDO-1 in most cancer types, IDO-2 in many cancer types, and TDO-2 in a few cancer types. High mutation burden in ER+ HER2− breast cancer, and ERV3-2 expression in ER− HER2− and HER2+ breast, colon, and endometrial cancers were associated with over-expression of all three genes. These results may have important implications for guiding development clinical trials of IDO-1 inhibitors.